Fundamentals Of Entreprenuerships ENT300 Business Plan : Online Clothing Store (Shibusa) / Nur Aiman Rafiqah Abd Rahman - Rafiqah Abd Rahman, Nur Aiman (2019)
Shibusa.Co are offering hoodies that focusing on customer comfort. Our hoodies will be come out in various colours. We also provide embroideries and patches to put at the hoodies as well we also offering the customers to custom made their design to the hoodies